Quality of colonoscopy practice: a single-center experience in Egypt - Ahmed S Gado; Basel A Ebeid; Aida M Abdelmohsen; Tarek S Gado; Anthony T Axon (SpringerOpen, 2016)
Background Colonoscopy is a technically demanding procedure with the potential to cause harm if its performance is suboptimal. It is incumbent on endoscopists, therefore, to evaluate their practices and to make improvements wherever possible. Bolak Eldakror Hospital is a secondary-care governmental hospital in Egypt in which we set up an endoscopy quality-assurance program in 2003. Aim The aim of this study was specifically to evaluate the quality of colonoscopy practice in our endoscopy unit and by publishing our experience to encourage others to develop a quality-improvement program. Patients and methods Predetermined international quality indicators for colonoscopy were employed to monitor the standard of endoscopic procedures between 2010 and 2014. Recorded information included all medical and technical details. Results A total of 286 colonoscopies were assessed. The main indication of colonoscopy was hematochezia (58.7%). Polyps were the main endoscopic findings (34.6%). Conscious sedation was used in 56.6%. Cecal intubation was achieved in 77.6%. The adjusted cecal intubation was 94%. Image documentation of cecal intubation was achieved in 92.3% examinations reaching the cecum. Mean cecal intubation time was 17.4±10 min. Mean withdrawal time was 6.6±4 min. The main reasons for unsuccessful cecal intubation were impassable mass or stricture in 23 (8%) colonoscopies and poor bowel preparation in 23 (8%). Colon preparation was rated adequate in 66.4%. Diagnostic colorectal biopsies for those with persistent diarrhea were obtained in 97%. Polyp detection rate was 36.1% and adenoma detection rate was 5.3%. Polypectomy was carried out in 89 (93.6%) patients with detected polyp/s. Retrieval of all excised polyps was successful in 84.3%. Postpolypectomy perforation occurred in one (0.4%) patient. Conclusion A high standard of colonoscopy can be achieved by the rigorous application of quality-assurance measures.